ANALISIS AKTIVITAS DAN HASIL BELAJAR SISWA DALAM PELAKSANAAN PEMBELAJARAN BERBASIS E LEARNING DI SEKOLAH DASAR NEGERI 3 RASAU JAYA - Sugiyono (Nusa Putra University, 2020)
This study aims to describe the activities and learning outcomes of students in the implementation of e learning-based learning in elementary schools 3 Rasau Jaya. This research is a descriptive study with a quantitative approach. The subjects in this study were elementary school students 3 Rasau Jaya. Data collection for this study was carried out through: (1) Observation sheets were used to examine student learning activities in implementing e-learning based learning; (2) The value of student learning evaluation is used to examine student learning outcomes after implementing e learning based learning. Data about student learning activities were analyzed using a percentage formula. Data about student learning outcomes are analyzed by calculating the average. Based on the research results, it was found that aspects of student learning activities 74,12. From these data it can be seen that student learning activities in the e learning learning process are in the sufficient category, student learning outcomes data have an average of 82,21. From these data it can be seen that student learning outcomes in the e learning learning process are in the good category.